Strategic Ambiguity and Arms Proliferation - Baliga, Sandeep; Sjöström, Tomas (Journal of Political Economy, 2008)
A big power is facing a small power that may have developed weapons of mass destruction. The small power can create strategic ambiguity by refusing arms inspections. We study the impact of strategic ambiguity on arms proliferation and welfare. Strategic ambiguity is a substitute for actually acquiring weapons: ambiguity reduces the incentive for the small power to invest in weapons, which reduces the threat of arms proliferation. But strategic ambiguity hides information, and this can lead to costly mistakes. Cheap‐talk messages can be used to trigger inspections when such mistakes are particularly costly. Tough messages that trigger inspections always imply a greater risk of arms proliferation.